Outcomes of Medical and Surgical Management in Aqueous Misdirection Syndrome - AlQahtani,Reham Dakam; Al Owaifeer,Adi Mohammed; AlShahwan,Sami; AlZaben,Khawlah; AlMansour,Raghad (Clinical Ophthalmology, 2023)
Reham Dakam AlQahtani,1 Adi Mohammed Al Owaifeer,1,2 Sami AlShahwan,1 Khawlah AlZaben,1 Raghad AlMansour3 1King Khaled Eye Specialist Hospital, Riyadh, Saudi Arabia; 2Ophthalmology Unit, Department of Surgery, College of Medicine, King Faisal University, Al-Ahsa, Saudi Arabia; 3College of Medicine, Imam Mohammed bin Saud University, Riyadh, Saudi ArabiaCorrespondence: Adi Mohammed Al Owaifeer, Ophthalmology Unit, Department of Surgery, College of Medicine, King Faisal University, P.O. Box 400, Al-Ahsa, 31982, Saudi Arabia, Tel +966135808573, Fax +966135800820, Email aalowaifeer@kfu.edu.saPurpose: To report the outcomes of medical and surgical management in patients diagnosed with aqueous misdirection syndrome (AMS).Patients and Methods: A retrospective chart review of all cases diagnosed with AMS at a single tertiary care eye center during the period from 2014 to 2021. Outcome measures were anatomical success (deepening of the anterior chamber (AC)), functional success (improvement in visual acuity), and treatment success (control of intraocular pressure (IOP)).Results: A total of 26 eyes with AMS from 24 patients were included. The patients were followed for a mean duration of 24 ± 18 months. Although some patients initially responded to medical and laser therapy, all but one (3.8%) eventually required surgery during the first 3 months after presentation. The mean duration from presentation until surgery was 45.9 ± 45.8 days (range: 2– 119 days). The majority of cases (69.2%) were managed by pars plana vitrectomy. At the last follow-up visit, anatomical success was achieved in 20 (76%) eyes, 15 (57%) eyes had a final visual acuity that was either similar to or better than baseline, and successful control of IOP was achieved in 17 (65%) eyes. Univariate analysis revealed that a history of trabeculectomy as a cause of AMS was a risk factor for treatment failure (OR, 7.8; 95% CI, 1.16– 52.35; P, 0.02).Conclusion: Our findings indicate that medical and laser management of AMS provide temporary control, and ...